Domain analysis for knowledge organization tools for ontology extraction - Smiraglia, Richard P. 1952- (Waldham, MA : Chandos Publishing is an imprint of Elsevier, 2015)
Domain analysis is the process of studying the actions, knowledge production, knowledge dissemination, and knowledge-base of a community of commonality, such as an academic discipline or a professional community. The products of domain analysis range from controlled vocabularies and other knowledge organization systems, to scientific evidence about the growth and sharing of knowledge and the evolution of communities of discourse and practice.In the field of knowledge organization- both the science and the practice domain analysis is the basic research method for identifying the concepts that will be critical building blocks for knowledge organization systems. This book will survey the theoretical rationale for domain analysis, present tutorials in the specific methods of domain analysis, especially with regard to tools for visualizing knowledge domains.
Includes bibliographical references and index.
Keywords: Information organization -- Technological innovations